2018
DOI: 10.1016/j.celrep.2018.02.006
|View full text |Cite
|
Sign up to set email alerts
|

P2RY1/ALK3-Expressing Cells within the Adult Human Exocrine Pancreas Are BMP-7 Expandable and Exhibit Progenitor-like Characteristics

Abstract: SUMMARYTreatment of human pancreatic non-endocrine tissue with Bone Morphogenetic Protein 7 (BMP-7) leads to the formation of glucose-responsive β-like cells. Here, we show that BMP-7 acts on extrainsular cells expressing PDX1 and the BMP receptor activin-like kinase 3 (ALK3/BMPR1A). In vitro lineage tracing indicates that ALK3+ cell populations are multipotent. PDX1+/ALK3+ cells are absent from islets but prominently represented in the major pancreatic ducts and pancreatic duct glands. We identified the puri-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 44 publications
0
41
0
Order By: Relevance
“…Likewise, P2Y 1 R expression has been demonstrated in lacrimal acinar cells and myoepithelial cells by RT-PCR, immunofluorescence and measurement of P2Y 1 R agonist-induced [Ca 2+ ] i increases, but further functional analyses are lacking (Ohtomo et al, 2011). Interestingly, the P2Y 1 R has been used as a surrogate cell-surface marker for the nuclear protein pancreatic duodenal homeobox 1 (PDX1) to isolate progenitor-like ductal cells from human pancreatic tissues, although no functional role for P2Y 1 Rs was investigated (Qadir et al, 2018). In contrast, studies on endocrine pancreas function suggest a role for P2Y 1 Rs in mediating insulin secretion from β cells (Leon et al, 2005;Petit et al, 2009).…”
Section: The Role Of P2 Receptors In Salivary Gland Functionmentioning
confidence: 99%
“…Likewise, P2Y 1 R expression has been demonstrated in lacrimal acinar cells and myoepithelial cells by RT-PCR, immunofluorescence and measurement of P2Y 1 R agonist-induced [Ca 2+ ] i increases, but further functional analyses are lacking (Ohtomo et al, 2011). Interestingly, the P2Y 1 R has been used as a surrogate cell-surface marker for the nuclear protein pancreatic duodenal homeobox 1 (PDX1) to isolate progenitor-like ductal cells from human pancreatic tissues, although no functional role for P2Y 1 Rs was investigated (Qadir et al, 2018). In contrast, studies on endocrine pancreas function suggest a role for P2Y 1 Rs in mediating insulin secretion from β cells (Leon et al, 2005;Petit et al, 2009).…”
Section: The Role Of P2 Receptors In Salivary Gland Functionmentioning
confidence: 99%
“…For example, population expressing P2RY1 and ALK3 (P2RY1+/ALK3+) has been found in the pancreatic ducts and ductal glands. This cell population expresses PDX1 and NKX6.1 indicating the existence of a new source of insulin secreting cells in the pancreatic ducts [44]. In addition, pancreatic exocrine tissue and other pancreatic endocrine cell types have also been shown to transdifferentiate to INS+ cells [43,[45][46][47].…”
Section: Generation Of Pancreatic Progenitors and Beta Cells From Hummentioning
confidence: 96%
“…The duct offers once again a good example of this ultimate limitation of LT: In 2008, it was reported that cells expressing the archetypal mature ductal marker carbonic anhydrase II (CAII) were progenitors [42]. A few years later, using LT in vitro , Klein and colleagues specifically discarded CAII + cells as a source of new β-cells [43], showing instead the multipotency of CAII − subpopulations [44], This apparent contradiction could be easily explained away by citing the usual LT shortcomings, including technical problems with CAII tagging, or, in this case, the fact that the first study was conducted in mice and the second with human cells. However, the CAII − cells described by Qadir and colleagues were found in major ducts and pancreatic duct glands (PDGs), interspersed between “regular” CAII + cells.…”
Section: On-demand Progenitor Cells?mentioning
confidence: 99%
“…Still, given the extraordinarily low natural turnover of β-cells in humans, additional interventions may be necessary to boost regeneration. In this context, bone morphogenetic proteins (BMPs) have been proven to stimulate pancreatic progenitor cell proliferation in mice [63] and humans [43, 44] by activating the BMP signaling pathway and inducing Inhibition of Differentiation (ID) proteins. Resident pancreatic pericytes secrete high levels of BMP proteins [64], suggesting the potential existence of local BMP signaling loops in the murine organ.…”
Section: Can These Regenerative Pathways Be Harnessed?mentioning
confidence: 99%